Pengabdian Masyarakat dalam Merealisasikan Pengembangan Usaha Berbasis Marketing Public Relation (MPR) - Heriana, Tutik; Nasrulloh Saputro, Agung; Fauzan, Imam; Neti Purwandari, Sri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: UD. Matha Computer Hebat as a partner is one of the MSMEs in Ponorogo Regency that has quality products and services. This business faces challenges in terms of marketing and expanding its market reach. The purpose of the service at UD. Matha Computer Hebat is to develop a marketing strategy through a Marketing Public Relations (MPR) approach so that can, 1) Increase public awareness (Brand Awareness) about products and services. 2) Create a good and positive image in the eyes of consumers and society. 3) Encourage customers to buy goods or use the services provided. 4) Improve effective communication between the company and the customer. Method: The service uses Participatory Action Research with Participatory Rural Appraisal, which focuses on empowerment, because empowerment must produce three things at once, namely increasing diversity in society and knowledge, solving practical problems, and transforming society through diversity. Results: Marketing public relations at UD. Matha Computer Hebat has implemented three strategies: Pull Strategy, Push Strategy, and Pass Strategy in developing its business. Conclusions: By realizing Marketing Public Relations (MPR), UD.Matha Computer Hebat can increase brand awareness, gain a positive image, expand market reach, and build better relationships with consumers so that it is able to achieve its long-term goals to advance and compete in an increasingly competitive market.